Growing up the Religious Potential from Religious Community of Qadiriyah wa Naqsyabandiyah Dawe Kudus - Danusiri Danusiri (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
This research focused on the congregation of the Qadiriyah wa Naqsyabandiyah in Piji, Dawe, Kudus, particularly on how they make any effort to make their potentials of religious observance can maximally grow. In order to find out their efforts, the writer applied participatory observation and was involved in their daily lives. The data were then organized in certain way according to the theme previously deter- mined. In order to achieve the maximum of religious observance which they call as wuṣūl dan wilāyah, the congregation of Qadiriyah wa Naqsyabandiyah use a series of rituals namely baiat (allegiance), zikir (remembrance), khataman ratib (complet- ing ratib), muraqabah, khalwat (seclusion), fida’, manaqib, and performing pilgrim- age to the grave of wali (muslim saints).